Enhancing Arabic Speaking Skills: The Role of Language Teachers - Wibawa, Putra; Thohri, Muhammad; Mujib, Lalu Supriadi bin (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
Mastery of speaking skills (maharah kalam) is a crucial component in Arabic language learning, particularly at MA Plus Ponpes Abu Hurairah Mataram. However, many students still face challenges in achieving effective oral proficiency. This study aims to examine the role of Arabic language teachers in enhancing students’ speaking skills and to identify the strategies they employ to support this goal. Using a qualitative field research approach, data were collected through observation, interviews, and documentation. The analysis was conducted descriptively. The findings reveal that teachers who are part of the Language Department play a central role in improving students’ speaking abilities through structured programs implemented on daily, weekly, monthly, and yearly bases. These include the use of communicative teaching methods, real-life speaking practices, and continuous feedback. Furthermore, the presence of a supportive learning environment significantly contributes to the development of students' oral proficiency. This study highlights the importance of teacher-led strategies and a conducive environment in fostering effective Arabic speaking skills among students